Emotional intelligence on health behaviours among Malaysian university students in a Malaysian public university: the mediating role of self efficacy - Omar Dev, Roxana Dev; Tengku Kamalden, Tengku Fadilah; Soh, Kim Geok; Abdullah, Maria Chong; Mohd Ayub, Ahmad Fauzi; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
University students typically enter a dynamic transitional period of new independence from their parents that is characterized by many factors. These factors which involve social, financial, and environment elements, can be a burden to the students putting them at risk in negative health behaviours. Negative health behaviours among university students are a course of concern since they have a tendency to be carried into adulthood which can possibly cause the emergence of chronic disease at a younger age. Self-efficacy is seen to increase with students’ emotional intelligence, together with better health behaviour. Therefore, the purpose of the study was to investigate the relationship between emotional intelligence and self-efficacy (mediator) on health behaviours among university students in Universiti Putra Malaysia, Malaysia. A correlational study was conducted on 400 undergraduate university students who lived on campus and were chosen through stratified random sampling technique using closed ended questionnnaires (Schutte’s Self Report Emotional Intelligence, General Self Efficacy Scale and a modified version of Health Style Questionnaire). Structural equation modelling was used to explore association between these aspects. Emotional intelligence, self-efficacy and health behaviour were significantly correlated and self-efficacy showed a partial mediation effect towards the relationship between emotional intelligence and promoting health behaviour (p=0.0001). Thus, there was an association between emotional intelligence with health behaviour, and emotional intelligence partially mediated this relationship. It is interpreted that emotional intelligence can boost positive health behaviour and emotional intelligence associated with self-efficacy relevantly gives benefit to health behaviour. Such data have important implications for both health practice and policy especially for higher education institutions.